Dampak Pembatalan Penjelasan Pasal 43 Ayat (2) Undang-Undang Pengadilan HAM terhadap Penyelesaian Kasus-Kasus Pelanggaran HAM Berat Sebelum Tahun 2000 - Sujatmiko Sujatmiko (Badan Strategi Kebijakan Hukum, 2010)
The objective of this research is to examine and elaborate on the impact of the cancellation of the explanation of Article 43 paragraph (2) of Law Number 26 Year 2000 About Court of Human Rights (HAM) on the mechanisms and the role of the House of Representatives (DPR) in the formation of an ad hoc Human Rights Court and the settlement of cases of gross human rights violations which occurred before 2000, especially the cases of human rights violations which already being investigated by the National Commission on Human Rights (Komnas HAM). The research is an eksplanatory research. The research use a qualitative method of qualitative. Data collection techniques being used are literature studies by analyzing the legal materials, both primary legal materials or secondary legal materials and field studies carried out using in depth interview with informants handpicked among the prosecutors, judges, scholar, governmental institution, the ad hoc judges of Human Rights and National Human Rights Commission.The research results can be drawn some conclusions. First, the decision to the Court Number 18/PUU-V/2007 in fact did not eliminate the role of the parliament in the formation of an ad hoc human rights court. Second, the House of Representatives decision to recommend the establishment of an ad hoc Human Rights Court shall be based on the results of investigations conducted by Komnas HAM and the results of the investigations conducted by the Attorney General. Third, the formation mechanism of the ad hoc Human Rights Court began with the investigation by Komnas HAM, followed by an investigation by the Attorney General, afterwhich the investigation findings are submitted to Parliament for the recommended establishment of an ad hoc Human Rights Court by the president. And fourth, the cases of alleged human rights violations that already have been investigated by Komnas HAM should be followed up by the Attorney General's should the documentation of the cases meet the formal and material requirements. But if the Attorney General considers those documents to be incomplete formally and materially, the Attorney Court should provide guidance to the National Commission on Human Rights Commission, especially to explain the shortages are the result of the investigation.The recommendations can be given are, first, the decision of the Constitutional Court No. 18/PUU-V/2007 should be socialized, especially to the law enforcement officials and the legislature, because this decision has confirmed and clarified the role of the Parliament, Commission, and the Attorney General in recommending the establishment of an ad hoc human rights court by stressing that the decision should be based on the results of the investigations conducted by Komnas HAM and the investigation conducted by the Attorney General. Considering that the decision of the Constitutional Court are final, the need for socialization has become more evident. Second, the Attorney General's Office and National Human Rights Commission need to sit down together to compromise concerning the above decision of the Constitutional Court regarding the procedure and mechanism for investigations, as well as the standard that must be met for the transfer of a case of human rights violations in the past.